2022
DOI: 10.1002/fsn3.3039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synbiotic bread containing lactic acid on blood lipids and apolipoproteins in patients with type 2 diabetes: A randomized controlled trial

Abstract: Recently, the use of synbiotics for managing various diseases has dramatically increased. Synbiotics have been shown to be a good approach to influence the composition of the gut microbiota with positive health effects. Management of type 2 diabetes mellitus (T2DM) complications is one of the reasons for the ingestion of synbiotics and so the aim of the current study was to determine the effects of synbiotic bread intake on markers of lipid profile in T2DM patients. One hundred T2DM patients (age between 20 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Next, we removed 421 studies due to the following reasons: lack of required data as indicated in the inclusion/exclusion criteria, not having an appropriate control group, and co‐supplementation of probiotics and/or synbiotics with other active ingredients. However, there were some studies that were removed due to having the same sample of participants 60–83 and hence were treated as a single study. Finally, 200 unique RCTs with 220 effect sizes were included for quantitative and qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we removed 421 studies due to the following reasons: lack of required data as indicated in the inclusion/exclusion criteria, not having an appropriate control group, and co‐supplementation of probiotics and/or synbiotics with other active ingredients. However, there were some studies that were removed due to having the same sample of participants 60–83 and hence were treated as a single study. Finally, 200 unique RCTs with 220 effect sizes were included for quantitative and qualitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…There are limited clinical trials based on the potential synbiotic bread consumption on human health, which is mainly focused on the effect on patients with type 2 diabetes mellitus (T2DM) regarding insulin metabolism and serum high-sensitivity C-reactive protein [25], blood lipids [26,27], apolipoproteins [26], nitric oxide, biomarkers of oxidative stress, and serum liver enzymes [28]. According to results of a randomized, double-blind, controlled clinical trial, the consumption of synbiotic bread consisting of L. sporogenes and inulin through 3 times/day in a 40 g per serve for 8 weeks by T2DM patients (n = 27) led to a significant decrease in the levels of serum insulin, and thus, is beneficial for insulin metabolism [25].…”
Section: The Influence Of Potential Synbiotic Combinations In Breads ...mentioning
confidence: 99%
“…According to results of a randomized, double-blind, controlled clinical trial, the consumption of synbiotic bread consisting of L. sporogenes and inulin through 3 times/day in a 40 g per serve for 8 weeks by T2DM patients (n = 27) led to a significant decrease in the levels of serum insulin, and thus, is beneficial for insulin metabolism [25]. Ghafouri et al [26] revealed that a decrease in total cholesterol levels and Apo A1 was observed in the patients with T2DM (n = 25) who consumed synbiotic bread, which is composed of B. coagulans, β-glucan, and inulin, for three times in a day for 8 weeks. However, while triacylglycerol(s) and very low-density lipoprotein cholesterol were decreased, the high-density lipoprotein-cholesterol was increased, but the levels of total cholesterol and low-density lipoprotein-cholesterol were not significantly influenced (p > 0.05) with consumption of synbiotic bread including Lactobacillus sporogenes and inulin by diabetic patients (n = 26) [27].…”
Section: The Influence Of Potential Synbiotic Combinations In Breads ...mentioning
confidence: 99%